Comparative Efficacy of Pharmacological Treatments for Adults With Autosomal Dominant Polycystic Kidney Disease: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials - Tsukamoto, Shunichiro; Urate, Shingo; Yamada, Takayuki; Azushima, Kengo; Yamaji, Takahiro; Kinguchi, Sho; Uneda, Kazushi; Kanaoka, Tomohiko; Wakui, Hiromichi; Tamura, Kouichi (Frontiers in Pharmacology, 2022)
Background: Tolvaptan is the gold standard treatment for autosomal dominant polycystic kidney disease (ADPKD), while several other drugs have the potential to inhibit the progression of ADPKD. However, individual clinical trials may not show sufficient differences in clinical efficacy due to small sample sizes. Furthermore, the differences in therapeutic efficacy among drugs are unclear. Herein, we investigated the effect of the ADPKD treatments. Method: We systematically searched PubMed, Medline, EMBASE, and the Cochrane Library through January 2022 to identify randomized controlled trials in ADPKD patients that compared the effects of treatments with placebo or conventional therapy. A network meta-analysis was performed to compare the treatments indirectly. The primary outcomes were changes in kidney function and the rate of total kidney volume (TKV) growth. Results: Sixteen studies were selected with a total of 4,391 patients. Tolvaptan significantly preserved kidney function and inhibited TKV growth compared to the placebo (standardized mean difference [SMD] [95% confidence interval (CI)]: 0.24 [0.16; 0.31] and MD: −2.70 [−3.10; −2.30], respectively). Tyrosine kinase inhibitors and mammalian target of rapamycin (mTOR) inhibitors inhibited TKV growth compared to the placebo; somatostatin analogs significantly inhibited TKV growth compared to the placebo and tolvaptan (MD: −5.69 [−7.34; −4.03] and MD: −2.99 [−4.69; −1.29], respectively). Metformin tended to preserve renal function, although it was not significant (SMD: 0.28 [−0.05; 0.61], P = 0.09). Conclusion: The therapeutic effect of tolvaptan was reasonable as the gold standard for ADPKD treatment, while somatostatin analogs also showed notable efficacy in inhibiting TKV growth.